2006
DOI: 10.1111/j.1471-4159.2006.03680.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory signalling pathways involved in astroglial activation by unconjugated bilirubin

Abstract: During neonatal hyperbilirubinaemia, astrocytes activated by unconjugated bilirubin (UCB) may contibute to brain toxicity through the production of cytokines. As a first step in addressing the signal transduction cascades involved in the UCB-induced astroglial immunological response, we tested whether tumour necrosis factor (TNF)-a receptor 1 (TNFR1), mitogen-activated protein kinase (MAPK) and nuclear factor jB (NF-jB) would be activated in astrocytes exposed to UCB, and examined the profile of cytokine produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
77
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 108 publications
(85 citation statements)
references
References 79 publications
(124 reference statements)
6
77
1
1
Order By: Relevance
“…In addition, pro-inflammatory cytokines could further promote apoptosis. For example, there are studies certifying that TNF-␣ or IL-1␤ activates the apoptosis pathway (10,26,27). The current study demonstrated that UCB might up-regulate or directly interact with the cell surface TNF receptor 1 and IL-1 receptor 1 as a ligand, similar to TNF-␣ and IL-1␤.…”
Section: Protective Role Of Nf-b Inhibition In Kernicterusmentioning
confidence: 68%
See 1 more Smart Citation
“…In addition, pro-inflammatory cytokines could further promote apoptosis. For example, there are studies certifying that TNF-␣ or IL-1␤ activates the apoptosis pathway (10,26,27). The current study demonstrated that UCB might up-regulate or directly interact with the cell surface TNF receptor 1 and IL-1 receptor 1 as a ligand, similar to TNF-␣ and IL-1␤.…”
Section: Protective Role Of Nf-b Inhibition In Kernicterusmentioning
confidence: 68%
“…The current study demonstrated that UCB might up-regulate or directly interact with the cell surface TNF receptor 1 and IL-1 receptor 1 as a ligand, similar to TNF-␣ and IL-1␤. Intriguingly, this could induce NF-B activation and subsequently result in cell death and cytokine release; in turn, the increased secretion of TNF-␣ and IL-1␤ will again bind to TNF receptor 1 and IL-1 receptor 1, respectively, thus forming a vicious pathogenic cycle created by inflammation, which would exacerbate the inflammation and cell death (10,27,41). Therefore, many researchers have attempted to inhibit cytokine production as a therapeutic target for preventing bilirubin-mediated neurotoxicity.…”
Section: Protective Role Of Nf-b Inhibition In Kernicterusmentioning
confidence: 99%
“…27 Incubation of astrocytes with 50 mM UCB and 100 mM HSA resulted in a biphasic activation of TNFR1 during the 24 h observation period. 25 The early phase was detected as early as 15 min, peaking at 1 h, and the late phase occurred at 12 h. Although the early-phase activation may result from a direct interaction of UCB with the TNFR1, we speculate that the secondary activation may be attributed to the action of IL-1b and IL-6 produced during astrocyte exposure to UCB (Figure 1), which are known to upregulate TNFR1. 28 Downstream from the UCB-induced expression of TNFR1, a rapid and transient activation of p38 (1-2 h), JNK1/2 (1-4 h) and ERK1/2 (2 h) was observed, with nuclear translocation of NF-kB occurring from 1 h onward with a maximal localization in the nuclei of astrocytes of B12% at 4 h, 25 which was also observed for 100 mM UCB (unpublished data).…”
Section: Introductionmentioning
confidence: 91%
“…24 In our earlier report 4 we have shown that UCB induces an immunological response in astrocytes, even after a short treatment of 4 h. For longer incubation periods, secretion of TNF-a and IL-1b reached a maximum at 12 h with a sustained elevation at 24 h after UCB addition. 25 The release of IL-6 was suppressed in the first 4 h of astrocyte incubation with UCB. However, for prolonged astroglial exposure to UCB, IL-6 showed a maximum production at 18 h. In these conditions, incubation of astrocytes with 100 mM UCB in the presence of the same amount of HSA for 24 h led to a marked increase in necrosis (B40%) and apoptosis (B16%).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation